IMPLICATIONS OF OXIDATIVE STRESS IN END-STAGE KIDNEY DISEASE PATIENTS: A REVIEW OF CAUSATIVE MECHANISMS, CURRENT CONCEPTS - Liakopoulos, Vassilios; Varouktsi, Garyfallia; Tsinari, Ariti; Veljkovic, Andrej; Lazarevic, Gordana; Perisic, Zoran; Hadzi-Djokic, Jovan; Kocic, Gordana; Roumeliotis, Stefanos (Acta medicae Medianae, 2022)
Oxidative stress (OS), termed as the imbalance between antioxidants and pro-oxidants in favor of the latter, is highly prevalent in chronic kidney disease (CKD) even at early stages and is gradually increased, in parallel to deterioration of kidney function. In end-stage kidney disease (ESKD), OS is further aggravated and associated with various adverse outcomes, including atherosclerosis and cardiovascular disease. In this review, we aim to present the clinical implications of OS, the pathogenetic causative mechanisms and the potential therapeutic interventions in both hemodialysis and peritoneal dialysis patients.
Keywords: Cardiovascular Disease; Chronic Kidney Disease; End-Stage Kidney Disease; Hemodialysis; Oxidative Stress; Peritoneal Dialysis; Vitamin C; Vitamin E